2008
DOI: 10.3748/wjg.14.4296
|View full text |Cite
|
Sign up to set email alerts
|

“Melanosis” in the small and large intestine

Abstract: Deposition of pigment in the intestinal mucosa is commonly observed by the endoscopist, especially within the colon, and particularly during investigations for constipation. Pigment may also be detected in the small intestine. Although labeled as melanosis, electron microscopy and X-ray analytical methods have provided evidence that this pigment is not melanin at all, but lipofuscin. Often, herbal remedies or anthracene containing laxatives are often historically implicated, and experimental studies in both hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 6 publications
1
59
0
9
Order By: Relevance
“…Обращает на себя внимание неравномерная интенсив-ность пигментации, наиболее выраженная в слепой киш-ке и проксимальных отделах толстой кишки [3,[7][8][9]. Этот факт связывают с концентрацией в просвете прокси-мального отдела толстой кишки большого количества повреждающего вещества, например слабительного пре-парата или его производных.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Обращает на себя внимание неравномерная интенсив-ность пигментации, наиболее выраженная в слепой киш-ке и проксимальных отделах толстой кишки [3,[7][8][9]. Этот факт связывают с концентрацией в просвете прокси-мального отдела толстой кишки большого количества повреждающего вещества, например слабительного пре-парата или его производных.…”
Section: Discussionunclassified
“…Другой возможной при-чиной может выступать разная абсорбирующая способ-ность отделов толстой кишки. Наконец, имеют значение особенности топографического распределения макро-фагов в толстой кишке [3,8]. Лимфоидные фолликулы, в норме представленные в слизистой оболочке, при меланозе не накапливают пигмент, поэтому ткань при-обретает вид «звездного неба», особенно в ректосигмо-идном отделе толстой кишки.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…7 Histochemical staining reactions of the pigment-laden macrophages in the lamina propria of human cases have demonstrated granule composition is not consistent with melanin pigment. 6 As a result, it has been suggested that pseudomelanosis coli may be a more appropriate name; 9 however, others refute this as an erroneous term, which means ''false black'' or ''not black,'' and suggest that melanosis coli is appropriate regardless of the pigment type. 5 Accordingly, for consistency, the authors have chosen to use the term melanosis coli to describe the discolored colorectal tissues in swine.…”
mentioning
confidence: 99%
“…6,8 Histologically, melanosis coli is characterized by accumulations of pigment-laden macrophages in the lamina propria of the colorectal mucosa. 7 Histochemical staining reactions of the pigment-laden macrophages in the lamina propria of human cases have demonstrated granule composition is not consistent with melanin pigment.…”
mentioning
confidence: 99%